Corrigendum: Diversity of the egg tertiary membranes in some elasmobranch species and comments on the actual yolk-sac viviparous reproductive mode : [RBMO 57(Especial): 102-121. <https://doi.org/10.22370/rbmo.2022.57.Especial.3302] - Oddone, Maria Cristina; Capapé, Christian (Revista de Biología Marina y Oceanografía, 2024)
This is a correction and reprint of Table 1 published on page 105 of the article “Diversity of the egg tertiary membranes in some elasmobranch species and comments on the actual yolk-sac viviparous reproductive mode”, published in the special issue Chondrichthyes of Revista de Biología Marina y Oceanografía 57(Especial): 102-121. <https://doi.org/10.22370/rbmo.2022.57.Especial.3302>